Adoption of Chemical Pesticides Under Commercial Vegetable Cultivation in Sri Ganganagar District of Rajasthan - Singh, Ajit; Jheeba, S. S.; Manjunatha, B. L.; Manjunatha, B. L.; Hajong, Dipika (Indian Journal of Extension Education, 2021)
The study was conducted in Sri Ganganagar district of Rajasthan to assess the extent of use of chemical pesticides under commercial vegetable cultivation. The primary data were collected from 100 farm households across 18 villages from 2016 to 2019. Chemical insecticides were used by all farmers whereas biopesticides and botanical pesticides were used by
Keywords: Over adoption; Chemical pesticide; Bio pesticide; Vegetables